Genetic variation and demographic history of Sudan desert sheep reveal two diversified lineages - Salim, B.; Alasmari, S.; Mohamed, N.S.; Ahmed, M.-K.A.; Nakao, R.; Hanotte, Olivier H. (2023)
More than 400 million sheep are raised on the African continent, the majority of which are indigenous and are primarily reared for sustenance. They have effectively adapted to various climatic and production environments, surviving and flourishing. The genetic relationships among these sheep populations remain understudied. Herein, we sequenced the entire mitochondrial DNA control region of 120 animals from Hamary and Kabashi and their crossbreed (Hamary x Kabashi) of Sudan desert sheep (SDS) to understand their maternal-inherited genetic variation and demographic history profiles and relate those to the history of sheep pastoralism on the African continent. The results show a diversified and predominant D- loop haplogroup B (n = 102, 85%), with all other sequences belonging to haplogroup A. Most of the maternal genetic variation was partitioned between haplogroup (76.3%) while within haplogroup accounted for 23.7% of the variation. However, little genetic differentiation was observed among the two breeds and their crosses, with our results supporting a Hamari maternal origin for the crossbreed. Bayesian coalescent-based analysis reveals distinct demographic history between the two haplogroups, two breeds and their crosses. Comparison of the two haplogroup showed that haplogroup B experienced an earlier expansion than haplogroup A. Unlike the breed-based comparison, the expansion of the two breeds started roughly at the same time, around 6500 years ago, with Kabashi having a slightly greater effective population size. The maternal ancestors of SDS may have diverged before their introduction to the African continent. This study provides novel insights into the early history of these two main breeds of Sudan desert sheep and their crosses.